2019
DOI: 10.1039/c9sc03280k
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of energy of activation to supramolecular nanofibre formation reveals enthalpic and entropic effects and morphological consequence

Abstract: The dimensions of supramolecular fibres formed from a system that starts far from equilibrium because of fast solvent – anti-solvent mixing is determined by the balance between enthalpy and entropy in different solvent mixtures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…3) and consistent with incorporation of the organic anions between the layers of cationic amphiphile (Fig. 1) as we reported previously for Gel@TCPP, 11 although some of the organic anions may reside on the outer surface of the fibres. The rheological properties of these multicomponent gels also reflect the morphological changes.…”
Section: Multicomponent Gel Preparation and Characterisationsupporting
confidence: 90%
See 2 more Smart Citations
“…3) and consistent with incorporation of the organic anions between the layers of cationic amphiphile (Fig. 1) as we reported previously for Gel@TCPP, 11 although some of the organic anions may reside on the outer surface of the fibres. The rheological properties of these multicomponent gels also reflect the morphological changes.…”
Section: Multicomponent Gel Preparation and Characterisationsupporting
confidence: 90%
“…26 The reorganization of the fibres in certain solvent conditions is facilitated here as a result of similar effects, where the movement of the traveller is accompanied by path change. The possibilities of changing the supramolecular fibre nature through controlled mixing in these systems 11,27 and others opens a myriad of possibilities to modulate the dynamic nature of the systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These kinds of supramolecular assemblies are generally formed closer to equilibrium conditions than larger crystals, although nucleation and growth mechanisms can be similar. [80][81][82] A particularly interesting case of twisted fibers are those formed from a synthetic amphiphilic peptide (Figure 9) that evolves from one kind of morphology to another over time. [83] When dissolved in ultrapure water at 25 °C twisted ribbons form quickly.…”
Section: Twisted Aggregates Crystals and Stereochemistrymentioning
confidence: 99%
“…Herein, we have demonstrated how the solvent ratio affects the self-assembly and the properties of final aggregates of double chain cationic gemini imidazolium-based surfactant (1,3-bis­[(3-octadecyl-1-imidazolio)­methyl]­benzene dibromide (GBIB) and a double chain anionic surfactant diaoctyl sodium sulfosuccinate or Aerosol OT (AOT). Our previous study found that solvent ratios played an important role in aggregation behavior of pure gemini GBIB surfactant. , This cationic GBIB and anionic double chain AOT were mixed in different molar ratios in various E/W solvent ratios (30:70, 50:50, and 70:30). These CaSs were then characterized using dynamic light scattering (DLS) and field emission gun scanning electron microscopy (FEG-SEM).…”
Section: Introductionmentioning
confidence: 98%